SOFTWARE DEVELOPMENT OF KEYWORD SEARCH AND PERFORMANCE ANALYSIS OF KEYWORD PERSONALIZATION ALGORITHM IN LARGE RDF GRAPH - Norman Saviero, Jehian
Keyword search in a graph is a new research and start to be introduced at 2010. In this final report will be discussed about an approach to get (an) answer(s) from one or more keywords. This approach emphasizes finding the approximate resemblance of a graph using new metrics brought by Sinha and her colleagues. Still from the same researcher, to get candidate of the answer(s) in a large graph, will be used new graph that represent the large graph to speed up finding and to make easier to get simple form of candidate answer. After that, choose graph that more suitable to the user using approximation metrics from Sinha et al and take it to find the similar graph with the expected graph.